Goal-Directed Resuscitative Intervention During Pediatric Interfacility Transport. Issue 2 (April 2016) - Stroud, Michael H.; Sanders, Ronald C; Moss, M. Michele; Sullivan, Janice E.; Prodhan, Parthak; Melguizo-Castro, Maria; Nick, Todd
Abstract : Surv Anesthesiol 2016;60(2):68–69 Goal-directed therapy is an aggressive monitoring method tailored to improving outcomes in critically ill patients, especially those affected by systemic inflammatory response syndrome (SIRS). However, this form of therapy is not widely used outside tertiary care centers, despite evidence that out-of-hospital interventions can improve outcomes in this population of patients.